Bi-Level Coordinated Planning of Sectionalizing Switches and Tie Lines Considering Operation Mode Adjustment - Luo, Qiang; Li, Wangjun; Gao, Chong; Zhang, Junxiao; Chen, Peidong; Xu, Zhiheng; Peng, Xiangang; Lai, Chun Sing; Lai, Loi Lei (Frontiers in Energy Research, 2022)
Distribution utilities can flexibly control the distribution networks by allocating the automatic and remotely controlled sectionalizing switches (SSs) which work with tie lines (TLs) to speed up fault management and are alternative devices for distribution operation mode adjustment. Hence, the SSs and the TLs play an important role in distribution networks. In order to improve the reliability of power supply and achieve economic distribution network operation, this paper proposes a bi-level SSs and TLs planning model, which considers distribution operation mode adjustment to optimize the allocation of SSs and TLs. The upper level of the proposed model aims at minimizing the sum of the total investment cost, the customer interruption loss cost. and the line loss cost. The upper level identifies the number and location of the SSs and the TLs. With the planning scheme obtained from the upper level, the lower level of the model adjusts the distribution operation mode to minimize the distribution line loss. In addition, binary particle swarm optimization (BPSO) is used because it has stable convergence and effectively explores the search space. A second order cone programming (SOCP) is employed to reduce the complexity of model and improve the solving process by linearizing the reconstruction calculation of distribution network. Finally, simulation studies are conducted on bus 2 and bus 4 of RBTS standard test system to assess the feasibility of the proposed model. The stability and effectiveness of the model are verified through various comparisons.